Influence of Different Nanoparticles on Thermophysical Properties and Wear Resistance of Corn Oil-Based Cutting Fluid in MQL-CNC Milling Machining - Habiby, M. Nuril Anwar; Puspitasari, Poppy; Aminnudin, Aminnudin; Pramono, Diki Dwi; Fikri, Ahmad Atif; Ghazali, Mariyam Jameelah (Universitas Negeri Malang, 2025)
Vegetable oil-based cutting fluids have emerged as a promising innovation in machining operations, supporting the advancement of sustainable and eco-friendly manufacturing practices. This study delves into the development of a biolubricant derived from corn oil, enriched with 0.15% mass fractions of various nanoparticles, including calcium carbonate (CaCO3), copper oxide (CuO), and multi-walled carbon nanotubes (MWCNT). These nano-cutting fluids were applied through the Minimum Quantity Lubrication (MQL) method during CNC milling of AISI 1045 steel. The investigation focused on evaluating thermophysical properties, including density, thermal conductivity, and dynamic viscosity, as well as tool wear performance. The results demonstrated that CuO nanoparticles yielded the highest density, while MWCNT exhibited superior thermal conductivity and viscosity. Among all samples, the fluid with MWCNT showed the most effective performance in minimizing tool wear. This study highlights the potential of nanoparticle-enriched vegetable-based cutting fluids as high-performance, environmentally responsible alternatives to conventional mineral oil-based lubricants, promoting greener machining in the manufacturing industry.